Implementasi Metode Seleksi Fitur Untuk Penentuan Indikator pada Klasifikasi Kompetensi Pemetaan Kuadran 9 di Pemprov Jateng - Yudha Widi Harjanto; Harries Arizonia Ismail; Satrio Agung Prakoso (Pusat Riset dan Inovasi Nasional, 2025)
Quadrant 9 (nine) is a model of employee competency mapping which will be used as a strategy for developing talented individuals and individuals who have weaknesses. In addition, quadrant 9 (nine) is also used in succession planning by identifying anyone who has the potential to become a leader in the organization. This study aims to obtain a data mining algorithm with a more accurate selection feature to find indicators that affect the classification of quadrant 9 competencies. The Forward Selection feature selection algorithm based on Naive Bayes is proven to be accurate and effective in determining the most influential attributes, namely IQ/Thinking Capacity, Self-Management, Social Communication, Service Orientation, Decision Making, Managing Others with 79.10% accuracy results and is included in the